ETIOPATOGENIA ULCERULUI GASTRIC ŞI DUODENAL - USM ADMIN (Moldova State University, 2008)
A peptic ulcer disease is an ulcer of an area of the gastrointestinal tract that is usually acidic and thus extremely painful. Tobacco smoking, blood group, spices and other factors that were suspected to cause ulcers until late in the 20th century, are actually of relatively minor importance in the development of peptic ulcers. There is debate as to whether Stress in the psychological sense can influence the development of peptic ulcers. Burns and head trauma, however, can lead to "stress ulcers", and it is reported in many patients. A family history is often present in duodenal ulcers, especially when blood group O (I) is also present. Despite the finding that a bacterial infection is the cause of ulcers in 80% of cases, bacterial infection does not appear to explain all ulcers and researchers continue to look at stress as a possible cause, or at least a complication in the development of ulcers. Ulcers are not purely an infectious disease and the psychological factors do play a significant role. There is solid evidence that psychological stress triggers many ulcers and impairs response to treatment, while Helicobacter pylori is inadequate as a mono-causal explanation as most infected people do not develop ulcers. Psychological stress functions as a cofactor with Helicobacter pylori. A study of peptic ulcer patients showed that chronic stress was strongly associated with an increased risk of peptic ulcer, and a combination of chronic stress and irregular mealtimes was a significant risk factor.